2008
DOI: 10.1007/s11295-007-0126-9
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and annotation of the evergrowing locus in peach [Prunus persica (L.) Batsch] reveals a cluster of six MADS-box transcription factors as candidate genes for regulation of terminal bud formation

Abstract: Buds are specialized structures that protect fragile meristematic regions during dormancy and are part of the mechanism that plants use to survive unfavorable environmental conditions such as low temperature or dessication stress. The evergrowing (evg) mutant of peach [Prunus persica (L.) Batsch] does not form terminal vegetative buds in response to dormancy-inducing conditions such as short days and low temperatures, and the terminal meristems maintain constant growth (leaf addition and internode elongation).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
353
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(365 citation statements)
references
References 64 publications
11
353
0
1
Order By: Relevance
“…In other plants, dormancy and related cellular changes such as tissue water status, chilling and meristem growth are linked through the actions of the DAM (dormancy associated MADS box) and DREB (dehydration-responsive element binding proteins) genes [62][63][64][65], indicating that switchgrass orthologs of these genes will be reasonable targets for future study.…”
Section: Tiller Bud Development and Rhizome Nutrient Status In Tempermentioning
confidence: 99%
See 2 more Smart Citations
“…In other plants, dormancy and related cellular changes such as tissue water status, chilling and meristem growth are linked through the actions of the DAM (dormancy associated MADS box) and DREB (dehydration-responsive element binding proteins) genes [62][63][64][65], indicating that switchgrass orthologs of these genes will be reasonable targets for future study.…”
Section: Tiller Bud Development and Rhizome Nutrient Status In Tempermentioning
confidence: 99%
“…In several other plants, such as grasses with summer dormancy or tree buds with winter dormancy, spontaneous mutations or divergent selection can yield plants which lack dormancy [4,64,[80][81][82]. Depending on the environmental stress that is placed on these plants, responses can be neutral, positive or negative.…”
Section: Uncoupling Dormancy From Winter-survival In Switchgrassmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-length cDNA cloning of the MADSbox gene and phylogenetic analysis revealed that the gene was similar to the StMADS11 clade MADS-box genes of Arabidopsis, such as SHORT VEGETATIVE PHASE (SVP) and AGAMOUS-LIKE24 (AGL24) (Yamane et al, 2008). Bielenberg et al (2008) independently identified six StMADS11 clade MADS-box genes as candidate genes associated with terminal bud formation in peach. Early studies had identified a mutant that failed to cease growth and to enter dormancy under dormancy-inducing conditions in peach; this is known as evergrowing (evg) (USDA PI442380) and was first identified in southern Mexico (Rodriguez et al, 1994).…”
Section: ) Functional Characterization Of Dam Genesmentioning
confidence: 99%
“…Wang et al (2002) generated an F 2 mapping population for the segregating evg trait and found that evg was located in G1. Sequencing and expression analysis of the evg locus identified six StMADS11 (SVP/AGL24)-clade MADS-box genes as candidate genes associated with terminal bud formation in peach (Bielenberg et al, 2008). These were named DORMANCY-ASSOCIATED MADS-box 1-6 (DAM1-6) genes.…”
Section: ) Functional Characterization Of Dam Genesmentioning
confidence: 99%